Answer:
x =
![(-1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/imeyatoa7i32v4duieoy32vt1wc6edefu5.png)
Explanation:
The bold side will be the "first side" and the italics will be the "second side."
3x + 2x + 7 = 8x + 8
First, you add the variables from the first side of the equal sign together.
3x + 2x = 5
Now the equation becomes: 5x + 7 = 8x + 8
Then you're going to take the 7 from the first side and subtract it from the 8 on the second side.
8 / 5 x + 1
8-7 = 1
Now the equation becomes: 5x = 8x + 1
Subtract 8x from both sides
-3x = 1
Divide both sides by -3
x =
![(-1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/imeyatoa7i32v4duieoy32vt1wc6edefu5.png)